Subtropical Mode Water and Permanent Pycnocline Properties in the World Ocean. Issue 2 (20th February 2019) - Feucher, Charlène; Maze, Guillaume; Mercier, Herlé
Abstract: A global reference state of the subtropical mode water and permanent pycnocline properties for the 2000–2015 period is presented. The climatology is obtained from a pattern recognition algorithm applied to stratification profiles from the Argo global array. The stratification features are identified as permanent upper ocean pycnostad and pycnocline even when the seasonal pycnocline is developed. The climatology shows that both Northern Hemisphere subtropical gyres have a qualitatively very similar stratification structure. The permanent pycnoclines in the North Atlantic and North Pacific show two deep centers colocated with thick subtropical and subpolar mode waters. These centers coincide with modes in the density and stratification space. These deep pycnocline centers are separated by a region with a shallower and thinner permanent pycnocline that is located downstream of Western Boundary Current Extensions and upstream of Eastern Subtropical Fronts. This feature creates a remarkable double‐bowl pattern at the basin scale. In the subtropical gyres of the South Atlantic and South Pacific Oceans, the mode water and permanent pycnocline structures are characterized by two modes in the density and stratification space that, unlike in the Northern Hemisphere, do not necessarily correspond to deep and thick permanent pycnocline regions. In the subtropical gyre of the South Indian Ocean, a single mode is found to correspond to a single center in the western part of the gyre. This study also shows that away from these deep centers where the pycnocline depth almost follows isopycnals, the permanent pycnocline experiences significant thermohaline gradients that are not density compensated. Plain Language Summary: The vertical structure of the ocean is of great importance to understand the impact of climate changes on the global ocean because a larger density differences (i.e., increased stratification) between the upper and the deeper ocean can prevent anthropogenic excess of heat, and carbon, from reaching the abyssal ocean. Using data from autonomous Argo floats that sample the ocean properties (e.g., temperature and salinity) from the surface down to 2, 000 m, we describe the vertical structure of the ocean's surface layers at midlatitudes, where heat is mostly stored in the upper 1, 000 m. This new study shows for the first time (i) a strong dependence of the ocean properties of the surface layer with the ocean properties of the transition layer with the abyss and (ii) that this transition layer exhibits rapid changes in temperature and density when rising to the surface as well as in the center of the each oceans. These new results are a significant refinement to the classic depiction of the midlatitude ocean as a simple bowl of warm water separated from the abyss by a layer of constant density and thus provide an accurate benchmark for climate models to detect long‐term changes in the ocean vertical structure. Key Points: In each subtropical basin, the stratification pattern of a mode water pycnostad overlying a permanent pycnocline exists continuously throughout the gyre The pycnocline has a double‐bowl pattern with two deep centers colocated with thick mode waters and shallower in the center of the gyre The North Atlantic subtropical permanent pycnocline and mode waters are much deeper, thicker, and less stratified than those in other gyres